2024
DOI: 10.1039/d4ra00302k
|View full text |Cite
|
Sign up to set email alerts
|

Understanding erosion resistance mechanisms of sodium aluminate silicate hydrate in erosion environments: a molecular dynamics study

Qingyin Tang,
Mengqi Sun,
Xinghai Lu
et al.

Abstract: Sodium-aluminate-silicate-hydrate (NASH) gel, as the primary reaction product stimulated by alkali in silica-aluminum-rich minerals, influences the mechanical and durability properties of geopolymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Subsequently, Wang et al 26 conducted MD simulations on the adsorption of heavy metal ions by geopolymers and observed that the composition of the reaction products directly affects the adsorption of radioactive nuclides, with a lower Al/Si ratio corresponding to a stronger adsorption capacity. Tang et al 27 investigated the anti-erosion mechanism of NASH, and they found that in a salt solution, the adsorption sites inside NASH were able to trap external Na + ions, which retarded the decomposition or fracture of the three-dimensional network skeleton, which resulted in good resistance to sulfate erosion. These studies have focused on the interactions of geopolymers with other substances, but there are still fewer studies on the reaction processes of alkali-activated geopolymers.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Wang et al 26 conducted MD simulations on the adsorption of heavy metal ions by geopolymers and observed that the composition of the reaction products directly affects the adsorption of radioactive nuclides, with a lower Al/Si ratio corresponding to a stronger adsorption capacity. Tang et al 27 investigated the anti-erosion mechanism of NASH, and they found that in a salt solution, the adsorption sites inside NASH were able to trap external Na + ions, which retarded the decomposition or fracture of the three-dimensional network skeleton, which resulted in good resistance to sulfate erosion. These studies have focused on the interactions of geopolymers with other substances, but there are still fewer studies on the reaction processes of alkali-activated geopolymers.…”
Section: Introductionmentioning
confidence: 99%